2022
DOI: 10.3389/fimmu.2022.980805
|View full text |Cite
|
Sign up to set email alerts
|

Host and bacterial factors linking periodontitis and rheumatoid arthritis

Abstract: Observations from numerous clinical, epidemiological and serological studies link periodontitis with severity and progression of rheumatoid arthritis. The strong association is observed despite totally different aetiology of these two diseases, periodontitis being driven by dysbiotic microbial flora on the tooth surface below the gum line, while rheumatoid arthritis being the autoimmune disease powered by anti-citrullinated protein antibodies (ACPAs). Here we discuss genetic and environmental risk factors unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 207 publications
0
27
0
1
Order By: Relevance
“…For example, smoking enhances the combined effect of risk variants in HLA-DR4 and PTPN22 [16]. Last, the microbiome has also been implicated as a contributing factor to the pathogenesis of RA, adding yet another level of disease complexity and individual heterogeneity [17][18][19].…”
Section: The Problem As Illustrated Through the Lens Of Rheumatoid Ar...mentioning
confidence: 99%
“…For example, smoking enhances the combined effect of risk variants in HLA-DR4 and PTPN22 [16]. Last, the microbiome has also been implicated as a contributing factor to the pathogenesis of RA, adding yet another level of disease complexity and individual heterogeneity [17][18][19].…”
Section: The Problem As Illustrated Through the Lens Of Rheumatoid Ar...mentioning
confidence: 99%
“…Numerous clinical and epidemiological studies have established a connection between periodontitis and the severity of RA, despite the distinct cause of these two conditions. An enzyme unique to Porphyromonas gingivalis, known as peptidylarginine deiminase, has been proposed as a potential mechanistic link between this prominent periodontal pathogen and the onset of RA [21]. In a 2021 study utilizing sequencing to assess the microbial components of subgingival plaque, saliva, and tongue coating in patients with early RA, those at risk of RA (individuals with RA-related autoantibody-positive arthralgia), and healthy controls, the study identified higher relative abundances of Prevotella in saliva and Veillonella in tongue coating among both early RA and high-risk groups.…”
Section: Microbiome Dysregulation In Rheumatoid Arthritismentioning
confidence: 99%
“…Periodontitis, one of the periodontal diseases, is defined as inflammation of the tooth-supporting tissues and results in attachment loss and alveolar bone destruction [ 2 ]. Periodontitis starts with local inflammation in the oral cavity by colonizing pathogenic periodontal bacteria and with microbiota shift resulting from polymicrobial dysbiosis [ 3 , 4 ]. Dysbiosis can cause a host inflammatory response, thus leading to periodontitis and its consequences such as attachment loss and tooth loss [ 5 ].…”
Section: Introductionmentioning
confidence: 99%